Phytochemical Study, Hplc Analysis of Vitamins, and Elemental Mapping of Iraqi Cardaria Daraba L - Zughair, Duaa Abbas; Luma Amer Musa; Hala Hamid Hammadi (Universitas Muhammadiyah Sidoarjo, 2025)
Cardaria belongs to Brassicaceae family which was originally known as Cruciferae and is commonly referred to as mustard or Cabbage family. C.draba has numerous signifigant therapeutic activities including, carminative, antiscorbutic, antioxidant, and laxative. The presence of numerous significant secondary metabolites is responsible for this function. Alkaloids, flavonoids, saponins, terpenoids, tannins, and leucoanthocyanins are all found in the aerial parts of C.draba. Elemental microanalysis by electron-excited X-ray spectrometry is a powerful characterization technique that has more than 60 year history. It gives comprehensive details on the constituents of substances by interrupting the icharacteristic X-rays ithat are generated by the collision of the sample with the electron beam. Despite the medicinal importance of C.daraba, very little work has been done in Iraq to investigate their phytochemical constituents. the present study aims to screen the phytochemical compositions of the Iraqi grown plant and to identify the presence and amounts of essential elements Atomic absorption spectrophotometer (AAS) and iField iEmissioniScanning iElectron Microscopy with Energy Dispersive X-ray Spectroscopy (FESEM-EDS) were used to identify the elements present in the plant. The antioxidant activity was determined using the DPPH method while HPLC was used to determine the vitamins in the plant. Plant extract exhibited radical scavenging activity in a dose-related imanner in relation to the standard (ascorbic acid) and the IC50 value was 2.96 mg/ml. AAS analysis of Iraqi C.daraba revealed that the level of Fe, Zn, Cu, Ca, and Mg were 89, 46, 0.1, 13.5, and 21.5 ppm, respectively. FESEM-EDS mapping of the ethanoilc plant extract revealed the presence of oxygen (O), isodium (Na), ipotassium (K), ichlorine (Cl), silicon (Si), selenium (Se), strontium (Sr), and thalium (Th), with percent mass 58.42%, 3.26%, 4.73%, 3.09%, 19.48%, 1.73%, 5.62%, and 7.74% respectively. Highlights: Iraqi Cardaria daraba L. contains alkaloids, flavonoids, tannins, terpenoids, and saponins with notable antioxidant activity (IC₅₀ = 2.96 mg/ml). HPLC analysis revealed high levels of vitamin C (42.8 mg/ml) and vitamin A (49.8 mg/ml) in the plant extract. AAS and FESEM-EDS analyses confirmed the presence of essential elements such as Fe, Zn, Ca, Mg, Se, and Sr, supporting its medicinal potential.